A novel design and manufacturing method for compliant bistable structure with dissipated energy feature. (November 2020) - Pan, Diankun; Wu, Zhangming; Dai, Fuhong; Tolou, Nima
Graphical abstract: Unlabelled Image Abstract: In this paper, a novel design concept and manufacturing method for the compliant bistable structure is proposed. The pulsed laser technique is utilized as the manufacturing method for both the fabrication and the introduction of desired pre-stresses, simultaneously. Based on this concept, a novel bistable structure consisted of one pre-compressed main beam, and a pair of supporting beams is designed and fabricated. The deformation difference between the main beam and the supporting beams induced by laser heating residual stress make the main beam to buckle under the constraints of two supporting beams and possess a bistable feature. The bistable structures can be implemented into other devices in the form of cantilevers thanks to the internal integration of the buckled beam and the boundary conditions. The characteristics of this new bistable structure, including its stable shape and snap-through response, are investigated both experimentally and numerically. During the snap forth and back process with the snapping load of 19 mN and the required energy of 77 mN·mm, an impressive energy dissipation with a loss factor value of 0.3 exists. Finally, a parametric study was carried out to find the critical performance parameters. Highlights: A novel bistable structure is designed and fabricated successfully by the pulsed laser machining technique. The bistable structure can be mounted under the cantilever boundary and exhibits strong hysteresis and feature of energy dissipation. The bistability of the proposed structure can be adjusted by processing parameters and geometry parameters.